Economic diplomacy - عزوز عبد القادر (Latakia University Journal - Economic and Legal Sciences Series, 2022)
In light of the developments that the world is witnessing economically as well as politically, it has become impossible to separate politics from the economy, until the economy has become a major reason for the emergence of diplomatic relations between countries. The state internally through increasing production and many other means that aim to reach sufficiency and abundance. However, the economy also has an important external role in raising the power of states economically, and placing them among the ranks of the great states at the economic as well as political level.